Examining the Static and Dynamic Relationship Between Policy Rates and Stock Prices: A Panel Data Analysis - Hardia, Natasha Athira Keisha; Rezeki, Gebrina (Grimsa Journal of Business and Economics Studies, 2024)
This study aims to examine the impact of the central bank’s interest rate on the stock price of the top five largest capitalization companies in Indonesia from January 2009 to December 2022. The research method employs both static and dynamic approaches, including Ordinary Least Squares (OLS), Robust Least Squares (RLS), Dynamic Ordinary Least Squares (DOLS), and Fully-Modified Ordinary Least Squares (FMOLS) methods. The results of econometric estimation align with the theory and this study's hypothesis, indicating that the increase of the central bank's interest rate negatively impacts company stock prices, especially in the long term. This valuable empirical evidence suggests that investors with a long-term perspective may need to reassess their portfolios in light of anticipated changes in monetary policy. Proactively monitoring these developments can help companies and investors make timely and well-informed decisions.